Exercise Interventions for Mental Well-Being and Academic Performance among University Students - Dr. Bhaskar Ankem, (The Bioscan, 2023)
University students face a particular combination of academic pressure, social change and uncertainty about the future, and concern about their mental well-being has grown steadily in recent years. At the same time there is a substantial body of evidence that regular physical activity benefits both the mind and the capacity to learn. This study examined the effect of a structured twelve-week exercise intervention on the mental well-being and academic performance of university students. A quasi-experimental design with a pre-test, a post-test and a control group was adopted. Sixty students were allocated to an experimental group, which took part in a supervised programme of moderate physical activity four times a week, and a control group, which continued its usual routine. Mental well-being was assessed through a recognised well-being scale, a perceived stress scale and a measure of sleep quality, while academic performance was assessed through grade point average, academic self-efficacy, self-reported concentration and class attendance. Paired and independent t- tests were used for analysis at the five per cent level of significance. The experimental group showed significant improvements in every measure of mental well-being and in every measure of academic performance, whereas the control group changed little. The findings indicate that a modest, regular exercise programme can meaningfully improve both the psychological health and the academic outcomes of university students, and they support the integration of physical activity into student life as a low-cost and broadly beneficial measure.